(untitled) (Polis (Santiago), 2018)
Around the world there are a multitude of regenerative community initiatives trying to respond to the multidimensional crisis. They take for granted the fact citizen’s action is essential in the process of social change. Among these, Transition Initiatives (TI) are an example that is especially important for its prevalence, creativity, and growth. TI’s try to strengthen local self-sufficiency and community resilience in the face of peak oil and climate change.This article begins with a synthesis of the global situation and continues with an analysis of the strengths and limitations of TI’s. The analysis is based on TIs in very different contexts (in País Vasco localities, in the city of Portland in the United States, and in the Bio-Bio region in Chile) as well as the authors’ own participation in the Transition movement.